PERAN CAREGIVER TERHADAP EFEKTIVITAS BALANCE EXERCISE UNTUK MENGURANGI RISIKO JATUH PADA LANSIA - Aisyah Maharani Putri Hutomo; Dinasti Pudang Binoriang (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2024)
An elderly person is someone who has experienced a decline in body function. This decrease in body function can cause incidents of falls in the elderly so that it has an impact on experiencing injury or even resulting in death. One of the ways to prevent the risk of falling is balance exercise. To see the effect of balance exercise to improve the body balance of the elderly so as to reduce the incidence of fall risk and the role of caregivers in assisting during intervention. This study uses a descriptive case study method. The results of the Up and Go test before the intervention were given a score of 23 and the resultsof the Side by Side assessment were obtained that the elderly could not do full tandem for 10 seconds. After 4 interventions for a week, the Up and Go test score was found to have decreased to 20 and the results of the Side by Side assessment were obtained that the elderly were still unable to do a full tandem for 10 seconds. The results of the study show that balance exercise has not affected the level of balance of the elderly because the period of time is not optimal.